Dampak Negatif Budaya Asing Terhadap Gaya Hidup Remaja Kota Makassar - Nur Islamiah (Jurnal Berita Sosial, 2022)
Foreign culture has a negative impact on the lifestyle of young people in Makassar City. This type of research is qualitative, with a sociological approach. Primary data sources and secondary data sources, data collection methods by conducting observations, interviews, documentation and library research. The instruments used were interview guides, documentation tools, stationery and tape recorders. Data processing and analysis techniques include data reduction, data presentation, and drawing conclusions. The results of this study describe the negative impact of foreign culture on the lifestyle tendencies of teenagers, namely: 1) The tendency towards fashion (fashion) which begins to follow negative ways of dressing foreign cultures, such as revealing their genitals, then cosplay lovers, namely the community that uses costumes. certain things and spend a lot of money just for things that can be said to be less useful, so teenagers tend to live hedonistic lifestyles that spend money just to splurge. 2) Tendency to deviate behavior, among others: Consuming illegal drugs, not good at socializing, in this case teenagers who are not good at choosing friends, will easily fall for it, for example friends who invite them to consume drugs, drink alcohol and also go clubbing. 3) Social Media Trends. 4) Behavioral tendencies in celebrating special foreign cultural days, such as: Valentine's Day celebrations, New Year's Eve celebrations, April Fool's Day celebrations, and Halloween day celebrations.